The Interaction of Botrocetin with Normal or Variant von Willebrand Factor (Types IIA and IIB) and Its Inhibition by Monoclonal Antibodies that Block Receptor Binding - Fujimura, Y; Miyata, S; Nishida, S; Miura, S; Kaneda, M; Yoshioka, A; Fukui, H; Katayama, M; Tuddenham, E G D; Usami, Y; Titani, K (Thrombosis and Haemostasis, 1992)
We have recently shown the existence of two distinct forms of botrocetin (one-chain and two-chain), and demonstrated that the two-chain species is approximately 30 times more active than the one-chain in promoting von Willebrand factor (vWF) binding to platelet glycoprotein (GP) Ib. The N-terminal sequence of two-chain botrocetin is highly homologous to sea-urchin Echinoidin and other Ca2+-dependent lectins (Fujimura et al., Biochemistry 1991; 30: 1957–64).Present data indicate that purified two-chain botrocetin binds to vWF from plasmas of patients with type IIA or IIB von Willebrand disease and its interaction is indistinguishable from that with vWF from normal individuals. However, an “activated complex” formed between botrocetin and IIB vWF expresses an enhanced biological activity for binding to GP Ib whereas the complex with IIA vWF has a decreased binding activity. Among several anti-vWF monoclonal antibodies (MoAbs) which inhibit ristocetin-induced platelet aggregation and/or vWF binding to GPIb, only two MoAbs (NMC-4 and RFF-VIII RAG:1) abolished direct binding between purified botrocetin and vWF. This suggests that they recognize an epitope(s) on the vWF molecule in close proximity to the botrocetin binding site.